Juglans mandshurica Maxim.: A Review of Its Traditional Usages, Phytochemical Constituents, and Pharmacological Properties - Luan, Fei; Wang, Zi y.; Yang, Yan; Lv, Hai z.; Han, Ke q.; Liu, Dao h.; Shang, Xiao f.; He, Xi r.; Zeng, Nan (Frontiers in Pharmacology, 2021)
Juglans mandshurica Maxim., also known as “Manchurian walnut” (Chinese) and “Onigurumi” (Japanese), is a medicinal plant widely distributed in Western and Central Asia, especially in China. It has been traditionally used to treat cancer, gastric ulcers, diarrhea, dysentery, dermatosis, uterine prolapse, and leukopenia. To date, more than 400 chemical constituents including quinones (e.g. naphthoquinones, anthraquinones, naphthalenones, tetralones), phenolics, flavonoids, triterpenoids, coumarins, lignans, phenylpropanoids, diarylheptanoids, and steroids, were isolated and structurally identified from different plant parts of J. mandshurica. Among them, quinones, phenolics, triterpenoids, and diarylheptanoids, as the major bioactive substances, have been extensively studied and displayed the best bioactivity. Recent pharmacological studies demonstrated that J. mandshurica and its active components exhibit a wide range of health-promoting properties, such as anticancer, anti-oxidant, anti-inflammatory, neuroprotective, anti-diabetic, immunomodulatory, antiviral, anti-melanogenesis, antimicrobial, and hepatoprotective activities. However, many investigations on biological activities were mainly based on crude extracts of this plant, and the bioactive ingredients responsible for these bioactivities have not been well identified. In addition, the further in vitro and in vivo studies on the mechanisms of action of the pure bioactive compounds and more elaborate toxicity studies as well as clinical studies are needed to ensure safety and effectiveness of the plant for human use. Taken together, the present review aims to provide comprehensively and systematically reorganized information on traditional usages, chemical constituents, pharmacological properties, pharmacokinetics, and toxicology of J. mandshurica, which will provide a useful bibliography for further investigations and applications of this plant in medicines and functional foods.